Effects of Psychotropic Medications Taken by Pregnant Women on Newborn Medical Condition and Lactation Method - Yuta Yoshino; Toru Yagi; Koichi Tsubouchi; Yusuke Takaishi; Yuki Ozaki; Jun‐ichi Iga; Keiichi Matsubara; Yuko Matsubara; Yuka Uchikura; Takashi Sugiyama; Shu‐ichi Ueno (Neuropsychopharmacology Reports)
ABSTRACT Background Maternal psychiatric condition during the perinatal period is relevant to children's cognitive development and mental health. Psychotropic medications are necessary to maintain the mental health of pregnant women with psychiatric disorders, but they are often avoided due to concerns about adverse effects, such as congenital malformations and abnormal neurodevelopment. A retrospective study of pregnant women with psychiatric disorders using psychotropic medications was performed to clarify maternal and child demographic data and to investigate whether psychotropic medications affected the Apgar score and the decision to breastfeed. Methods Data of pregnant women with psychiatric disorders who were referred from the Department of Obstetrics and Gynecology to the Department of Neuropsychiatry at Ehime University Hospital from January 2014 to December 2022 were collected retrospectively. Pearson's chi‐squared test and multiple regression analysis were used for statistical analyses. Results A total of 226 women were included; 194 gave birth at our hospital, of whom 79 (40.7%) were taking psychotropic drugs at the time of delivery. None of the children had malformations. There was no relationship between the use of psychotropic medications and the choice to breastfeed. Multiple regression analysis showed that only the gestational weeks at birth were significantly associated with birth weight (p < 0.001) and Apgar score (1 min: p = 0.030; 5 min: p = 0.044). Conclusions The use of psychotropic medications during the perinatal period appears safe and beneficial for both pregnant women with psychiatric disorders and their children, and breastfeeding should be considered even if the mother continues to take the medication. To clarify these points, prospective studies using large samples from several countries are needed.